Moral Responsibility for Protection of Nature - Kalenda, Česlovas (Problemos, 1990)
The problem of moral responsibility in the face of ecological catastrophe is discussed. The concepts of necessity and liberty are analysed. Based upon the analysis the context of the category “responsibility” is defined. The measure of responsibility of personality for the protection of nature is considered in the context of his activity and linked with the ecological requirements as the necessary condition of the development of society. The activity of personality in the protection of nature is said to be moral to the extent in which the personality apprehends the self-value of nature and turns the apprehension into the motive of his activity.